Study of silver ion migration from melt-blended and layered-deposited silver polyethylene nanocomposite into food simulants and apple juice - Jokar, Maryam; Abdul Rahman, Russly (Taylor & Francis, 2014)
Colloidal silver nanoparticles were prepared via chemical reduction using polyethylene glycol (PEG) as a reducing agent, stabiliser and solvent. Silver polyethylene nanocomposites were produced via two methods, namely: melt blending and layer-by-layer (LBL) deposition of silver nanoparticles onto a polyethylene film. The silver ion release from either melt-blended or LBL-deposited nanocomposites into a food simulant and apple juice during 30 days at 4°C and 40°C was determined by atomic absorption spectroscopy. The effects of incorporating or coating of silver nanoparticles, silver concentration, contact media, temperature and time on silver ion migration were evaluated using factorial design. The diffusion coefficients of silver ions into the food simulants and apple juice were calculated using the Miltz model. The results indicated that the production method of nanocomposite, silver concentration, temperature, time and contact media showed a significant effect (p < 0.05) on silver ion migration. The quantity of silver ion migration from the nanocomposites into the food simulants and apple juice was less than the cytotoxicity-level concentration (10 mg kg(-1)) in all cases over 30 days. The coating of silver nanoparticles, higher silver concentration in the nanocomposite, higher temperature and acidic property of contact liquid all promoted the silver ion release from the nanocomposite films. The migration of silver ions from nanocomposites obeyed first-order diffusion kinetics.